Routine Postoperative Computed Tomography Scans After Pelvic Fracture Fixation: A Necessity or a Luxury?. (February 2018) - Elnahal, Walid A.; Vetharajan, Niraj; Mohamed, Bashir; Acharya, Mehool; Chesser, Timothy J. S.; Ward, Anthony J.
Abstract : Introduction: There is no consensus regarding the postoperative radiology imaging protocol after pelvic fracture surgery. Some institutes routinely scan all patients after their surgery, others do not. The aim of this study was to assess the value of routine use of computed tomography (CT) scans after pelvic fracture surgery and to determine the sensitivity of conventional plain radiographs and intraoperative fluoroscopy in detecting metalwork malposition. Patients and Methods: The radiographs and clinical notes of patients undergoing pelvic fracture surgery in the period between January 2010 and December 2015 were reviewed. Patients were categorized into 2 main groups: group A—patients whose fixation entailed the use of a sacroiliac (SI) screws and group B—patients whose fixation did not require an SI screw. Furthermore, the patients were classified according to the position of metalwork in their postoperative plain radiographs and perioperative fluoroscopy into 3 groups: (1) Safe: When there was no suspicion of metalwork malposition. (2) Suspicious: When there was some suspicion of malposition but radiographs were inconclusive. (3) Definite: When plain imaging showed a definite malposition. Results: One hundred ninety-eight patients were included in this study (161 in group A and 37 in group B). In group A, 148 (92%) were classified as safe, 10 were suspicious (6%), and 3 (2%) showed definite malposition. Of the fractures that were believed to be safe on plain radiographs, 78% were confirmed to be safe on CT scans, whereas 22% showed malpositioned metalwork, and 7 patients (4%) required a revision surgery. Plain radiographs showed a sensitivity of 27% in detecting metalwork malposition and a specificity of 99%. Increasing the number of screws significantly increased the risk of malposition and reoperation ( P = 0.006 and 0.002 respectively). The plain images of group B were all classified as safe. The CT scans detected 2 cases with long metalwork protruding into the soft tissues, none of which required a revision surgery. Conclusion: Perioperative fluoroscopy and plain postoperative radiographs have a low sensitivity in detecting the metalwork malposition after pelvic fracture surgery. We recommend the use of routine postoperative CT scans in patients whose fixation entails the use of SI screws. In this series, routine scanning of patients who did not have SI screws added no significant clinical value. Level of Evidence: Level IV Diagnostic. See Instructions for Authors for a complete description of levels of evidence.